2019
DOI: 10.1073/pnas.1816582116
|View full text |Cite
|
Sign up to set email alerts
|

A SIR-independent role for cohesin in subtelomeric silencing and organization

Abstract: Cohesin is a key determinant of chromosome architecture due to its DNA binding and tethering ability. Cohesin binds near centromeres and chromosome arms and also close to telomeres, but its role near telomeres remains elusive. In budding yeast, transcription within 20 kb of telomeres is repressed, in part by the histone-modifying silent information regulator (SIR) complex. However, extensive subtelomeric repressed domains lie outside the SIR-binding region, but the mechanism of silencing in these regions remai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…In S. pombe , the Psc3 (Scc3 in budding yeast) cohesin subunit directly interacts with the heterochromatin protein Swi6, which ensures cohesin recruitment and cohesion establishment at centromeres but is also important to ensure the genomic integrity of the heterochromatic mating type locus [ 58 ]. Finally, cohesin is enriched in subtelomeric regions and is required for their transcriptional repression in both fission and budding yeast through mechanisms that remain to be deciphered [ 59 , 60 ]. How cohesin shapes these compacted regions and whether this influences gene expression or DNA repair remains an open question.…”
Section: Chromosome Organization Within the Nuclear Space And Cohesin...mentioning
confidence: 99%
“…In S. pombe , the Psc3 (Scc3 in budding yeast) cohesin subunit directly interacts with the heterochromatin protein Swi6, which ensures cohesin recruitment and cohesion establishment at centromeres but is also important to ensure the genomic integrity of the heterochromatic mating type locus [ 58 ]. Finally, cohesin is enriched in subtelomeric regions and is required for their transcriptional repression in both fission and budding yeast through mechanisms that remain to be deciphered [ 59 , 60 ]. How cohesin shapes these compacted regions and whether this influences gene expression or DNA repair remains an open question.…”
Section: Chromosome Organization Within the Nuclear Space And Cohesin...mentioning
confidence: 99%
“…Mutants affected in cohesin, a key architectural chromosomal protein complex, have been shown to display telomere silencing defects as well as Slt2-dependent Sir3 hyperphosphorylation. However, in this case, Slt2 activity contributed to derepression only to a very limited extent, suggesting the existence of a Sir-independent mode of repression mediated by cohesin [118]. Several studies with different organism models, including S. cerevisiae, have shown that sirtuins are linked to aging [119].…”
Section: Epigenetic Control Of Gene Expression and Yeast Life Span Ex...mentioning
confidence: 79%
“…In P. falciparum , the current genome‐wide chromosome conformation capture (Hi‐C) datasets do not provide evidence of typical enhancer‐promoter interactions found in other eukaryotes (Ay et al , 2014 ; Bunnik et al , 2019 ). Moreover, in S. cerevisiae , a cohesin mutant resulted in the de‐repression of genes located in subtelomeric regions, perhaps via disruption of local chromatin structure (Kothiwal & Laloraya, 2019 ). However, the invasion‐related genes affected by Pf SMC3 are scattered across the genome (Dataset EV21 ).…”
Section: Discussionmentioning
confidence: 99%